Exposure to Insecticides Reduces Populations of Rhynchophorus palmarum in Oil Palm Plantations with Bud Rot Disease - Martinez, Luis Carlos; Plata-Rueda, Angelica; Rodriguez-Dimate, Francisco Andres; Campos, Juliana Mendonca; Santos Junior, Valdeir Celestino dos; Rolim, Gabriela Da Silva; Fernandes, Flavio Lemes; Silva, Wiane Meloni; Wilcken, Carlos Frederico [UNESP]; Zanuncio, Jose Cola; Serrao, Jose Eduardo (Mdpi, 2019)
The South American palm weevil (SAPW), Rhynchophorus palmarum Linnaeus (Coleoptera: Curculionidae) is the main pest of Elaeis guineensis and damages palm trees with bud rot disease in the Americas. The effects of six neurotoxic insecticides (abamectin, carbaryl, deltamethrin, fipronil, imidacloprid and spinosad) were evaluated against SAPW for toxicity, survival, reproduction, and mortality. Abamectin (LC50 = 0.33 mg mL(-1)), Carbaryl (LC50 = 0.24 mg mL(-1)), deltamethrin (LC50 = 0.17 mg mL(-1)), and fipronil (LC50 = 0.42 mg mL(-1)) were the most toxic to SAPW. Adult survival was 95% without exposure to insecticides, decreasing to 78-65% in insects treated with the LC25 and 49-35% in insects exposed to LC50. Sublethal doses of carbaryl, fipronil and imidacloprid showed significant effect on the reproduction of this insect. Mortality of SAPW populations caused by insecticides had similar effects in the laboratory and field conditions. The results suggest that carbaryl, deltamethrin, fipronil, and imidacloprid caused significantly higher mortality as compared to the control in SAPW and may be used to control its populations in oil palm trees where bud rot appears as the key disease for SAPW attraction and infestation.
Keywords: effects on reproduction; insect pest-disease association; insecticide efficacy; neurotoxicity; pest control; survivorship